2020
DOI: 10.1177/1049909120902976
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Mortality Rates, and Treatments Received in Last Few Days of Life for Patients Dying in Intensive Care Units: A Multicenter Study

Abstract: Background: Information is presently lacking about the end-of-life care in intensive care unit (ICU). We explored the characteristics, mortality rates, and treatments received in the last few days of life for patients who died in ICU. Methods: This was a retrospective multicenter cohort study. We included patients who died from different medical illnesses between January 2014 and January 2017 in 8 medical ICUs across 3 major health-care systems in Jordan. Of 11 029 patients who were admitted for the study in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
1
6
1
3
Order By: Relevance
“…We found that the all-cause ICU mortality rate was 18.0%, which is lower than the mortality rate of 34.6% reported by a retrospective multicentre study conducted in Jordan from 2014 to 2017 [14]. e study noted that university hospitals such as the one in which we conducted this study had lower mortality rates.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…We found that the all-cause ICU mortality rate was 18.0%, which is lower than the mortality rate of 34.6% reported by a retrospective multicentre study conducted in Jordan from 2014 to 2017 [14]. e study noted that university hospitals such as the one in which we conducted this study had lower mortality rates.…”
Section: Discussioncontrasting
confidence: 65%
“…Some limitations and strengths of this study need to be addressed. First, the ICUs in which we conducted this study are not representative of all ICUs in Jordan, since academic hospitals often provide clinical capabilities unavailable in nonacademic hospitals [14,31]. Another limitation is the sample size; we were not able to achieve the desired sample size due to changes in the ICUs' structure (done in order to accommodate COVID-19 patients) which eventually led to termination of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Providing end‐of‐life care is challenging in a Jordanian intensive care context, which is attributed to the fraught of cultural issues including over‐optimistic hope, in addition to other religious and medico‐legal concerns (Almansour, 2015; Almansour, Ahmad, et al, 2020; Almansour et al, 2019). Khader (2017) summarises the main cultural challenges hindering the provision of palliative care services in Jordan.…”
Section: Introductionmentioning
confidence: 99%
“…Providing end-of-life care is challenging in a Jordanian intensive care context, which is attributed to the fraught of cultural issues including over-optimistic hope, in addition to other religious and medico-legal concerns (Almansour, 2015;Almansour, Ahmad, et al, 2020;Almansour et al, 2019). Khader (2017) of family and physicians to refer patients to palliative care because it might be considered a failure of their cure and (4) religious misconceptions leading the patient to suffer intolerable pain as a form of salvation that also often prevent them from seeking medical attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation